2017
DOI: 10.9734/ajee/2017/33070
|View full text |Cite
|
Sign up to set email alerts
|

Community Participation in Environmental Conservation and Protection: A Case study of Kida community, Hawul local Government Area of Borno State, Nigeria

Abstract: Environmental natural resource conservation and protection (ENRCP) has been extensively promoted in recent years as an approach for pursuing nature conservation and socioeconomic objectives. The rationale for ENRCP is often compelling and convincing. This article assesses the environmental problems, level of community participation and involvement of government in ENRCP and examine the problems associated with community participation in ENRCP. The study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Therefore, they need to be encouraged to start their project on conservation and be convinced that it would bring economic benefit in the long run. At the very least, it would provide more job opportunities for the villagers (Bassi et al 2017).…”
Section: Ladder Of Participationmentioning
confidence: 99%
“…Therefore, they need to be encouraged to start their project on conservation and be convinced that it would bring economic benefit in the long run. At the very least, it would provide more job opportunities for the villagers (Bassi et al 2017).…”
Section: Ladder Of Participationmentioning
confidence: 99%
“…The finding revealed that there is a significant deference between problems associated with indiscriminate tree felling, bush burning, overgrazing and ignorance among community members willingness in participation. Bassi et al (2017) recommended among others that Government important role is to boost community participation through replanting of trees, patrolling and employment of conservation workers. In addition public enlightenment should be given consideration to the community on the danger of not protecting and conserving the environment.…”
Section: Literaturementioning
confidence: 99%